Small-angle neutron scattering study of specific interaction and coordination structure formed by mono-acetyl-substituted dibenzo-20-crown-6-ether and cesium ions. Issue 8 (2nd August 2016) - Motokawa, Ryuhei; Kobayashi, Tohru; Endo, Hitoshi; Ikeda, Takashi; Yaita, Tsuyoshi; Suzuki, Shinichi; Narita, Hirokazu; Akutsu, Kazuhiro; Heller, William T.
Abstract : This study uses small-angle neutron scattering (SANS) to elucidate the coordination structure of the complex of mono-acetyl-substituted dibenzo-20-crown-6-ether (ace-DB20C6) with cesium ions (Cs + ). SANS profiles obtained for the complex of ace-DB20C6 and Cs + (ace-DB20C6/Cs) in deuterated dimethyl sulfoxide indicated that Cs + coordination resulted in a more compact structure than the free ace-DB20C6. The data were fitted well with SANS profiles calculated using Debye function for scattering on an absolute scattering intensity scale. For this theoretical calculation of the scattering profiles, the coordination structure proposed based on density functional theory calculation was used. Consequently, we conclude that the SANS analysis experimentally supports the proposed coordination structure of ace-DB20C6/Cs and suggests the following: (1) the complex of ace-DB20C6 and Cs + is formed with an ace-DB20C6/Cs molar ratio of 1/1 and (2) the two benzene rings of ace-DB20C6 fold around Cs + above the center of the crown ether ring of ace-DB20C6.